THE EFFECT OF VALUE-RELEVANCE INFORMATION BETWEEN EARNINGS AND CASH FLOW TOWARDS STOCK PRICE AT LQ45 COMPANY LISTED IN INDONESIA STOCK EXCHANGE - admin, Habibi Qurrata A?yuni B42112011 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This research aimed to determine the effect of value relevance information between earnings and cash flows towards the stock price by analyzing the stock price average abnormal return. This research is quantitative serves to test the hypothesis proposed in the research and answered the problem in the researchThe populations in this research are the company that is consistently listed for three consecutive years starting from 2012-2014 in the LQ45in Indonesia Stock Exchange (BEI). The sampling methods used in this research using purposive sampling method that has17 samples and 51 observations. Research uses secondary data and multiple regression analysisThe result of the research shows that there is significance influence between the value relevance information of the cash flows statements and earnings statements towards the stock price. Keywords: Stock Price, Cash Flows Statements, Earnings Statements.